STRATEGI ADAPTIF ORANG TUA BERDASARKAN LATAR BELAKANG PENDIDIKAN DALAM MEMBIASAKAN PHBS PADA ANAK USIA DINI - karunia, Aisah; roby naufal arzaqi; Nur Faizah Romadona; Ocih Setiasih (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2025)
Clean and Healthy Living Behavior (CHLB) is essential to be instilled from an early age, as it contributes significantly to the development of lifelong health habits. However, its implementation within families still encounters various challenges, particularly due to differences in parents educational backgrounds, levels of understanding, and socio-economic conditions. This study aims to explore the patterns of strategies used by parents in fostering CHLB in early childhood through a qualitative case study approach involving three mothers with different education levels and living environments. Data were collected through semi-structured interviews and analyzed using the Grounded Theory technique. The findings indicate that parents with higher education tend to adopt digital-based strategies, such as the use of educational videos and games, while parents with lower education rely more on traditional methods such as storytelling, modeling, and direct explanation. Challenges include limited time, financial constraints, and less supportive environments. The study emphasizes the importance of collaboration between schools and families to strengthen CHLB habituation in early childhood.